Synergistic role of hydrogen treatment and heterojunction in H-WO3-x/TiO2-x NT/Ti foil-based photoanodes for photoelectrochemical wastewater detoxification and antibacterial activity. (March 2023) - Mahadik, Mahadeo A.; Hwang, In-Seon; Chae, Weon-Sik; Lee, Hyun Hwi; Choi, Sun Hee; Cho, Min; Jang, J.S.
Abstract: The process of photoelectrochemical wastewater detoxification is limited by significant charge recombination, which is difficult to suppress with efficient single-material photoanodes. We demonstrated the effectiveness of hydrogen treatment in evaluating charge separation properties in WO3-x /TiO2-x NT/Ti foil heterojunction photoanodes. The influence of varying hydrogen annealing (200–400 °C) on the structural and photoelectrochemical properties of WO3 /TiO2 NS/NT heterojunction is studied systematically. Additionally, after hydrogen treatment of pristine WO3 /TiO2 NT/Ti foil photoanodes, substoichiometric H-WO3-x /TiO2-x NT-300 achieved the 1.21 mA/cm 2 photocurrent density, which is 8.06 and 3.27 times than TiO2 NT and WO3 /TiO2 NT. The hydrogen-treated H-WO3-x /TiO2-x NT-300 electrode exhibits 3 times greater bulk efficiencies than the WO3 /TiO2 NT electrode due to the production of oxygen vacancies at the interface. Additionally, optimum H-WO3-x /TiO2-x NS/NT-300 photoanode exhibited 93.8% E. coli and 99.8% BPA decomposition efficiencies. The present work shows the effectiveness of microwave-assisted H-WO3-x /TiO2-x NT heterojunction photoanodes for organic decomposition and antibacterial activity in a neutral environment without surface-loaded co-catalysts. Graphical abstract: Here, for the first time, we develop H-WO3-x /TiO2-x NT/Ti foil-based photoanodes by a simple microwave and anodization process. The optimum H-WO3-x /TiO2-x NT-300 exhibited 93.8% and 99.8% E. coli and BPA degradation in 180 min. Additionally, optimum photoanode achieved 8.06 times higher photocurrent density (1.21 mA/cm 2 ) than TiO2 NT. Image 1 Highlights: H-WO3-x /TiO2-x NT/Ti was developed via a simple surfactant-free microwave-process. PEC performance is enhanced by cooperation of defects and TiO2-x transport channels. H-WO3-x /TiO2-x NT-300 displayed 8 times higher photocurrent density than TiO2 NT. 93.8% E. coli and 99.8% BPA decomposition efficiency within 180 min. The charge transfer mechanism in H-WO3-x /TiO2-x NT-300 during PEC is well proposed.